2014
DOI: 10.1590/0034-7167.2014670517
|View full text |Cite
|
Sign up to set email alerts
|

Percepção materna quanto aos filhos recém-nascidos hospitalizados

Abstract: Cross-sectional descriptive study conducted in the neonatal unit of a public teaching hospital in the state of São Paulo, Brazil, which aimed to determine the perceptions of mothers about their newborns hospitalized children. The sample consisted of 100 women questioned, through the Neonatal Perception Inventory Broussard, about how much trouble was expected to be presented by babies of the general unit, on behaviors such as crying; feeding; regurgitate or vomit; evacuate; sleep and have a routine. Then, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
5
0
5
Order By: Relevance
“…A interação da mãe e da família no processo de fortalecimento do vínculo com o bebê deve ser gradativa e crescente. Para prevenir possíveis ameaças na construção do vínculo, o laço afetivo deve, sempre que possível, ser estável e harmônico (Cartaxo et al, 2014;Carmona et al, 2014). Estudos demostram que o sentimento de confiança, a sensação de Research, Society and Development, v. 9, n. 8, e198985610, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5610 segurança e o bem-estar são proporcionados e sentidos pelo neonato e contribuem de forma desejável no seu desenvolvimento (Samra et al, 2015;Gerstein, Poehlmann-Tynan, Clark, 2015;Spinelli et al, 2016).…”
Section: Resultsunclassified
“…A interação da mãe e da família no processo de fortalecimento do vínculo com o bebê deve ser gradativa e crescente. Para prevenir possíveis ameaças na construção do vínculo, o laço afetivo deve, sempre que possível, ser estável e harmônico (Cartaxo et al, 2014;Carmona et al, 2014). Estudos demostram que o sentimento de confiança, a sensação de Research, Society and Development, v. 9, n. 8, e198985610, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5610 segurança e o bem-estar são proporcionados e sentidos pelo neonato e contribuem de forma desejável no seu desenvolvimento (Samra et al, 2015;Gerstein, Poehlmann-Tynan, Clark, 2015;Spinelli et al, 2016).…”
Section: Resultsunclassified
“…Because of the benefits obtained in relation to the progress of the newborn, the active participation of family members, especially parents, should be encouraged and facilitated by the hospital and by the health team (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who experience difficulties to visit their children are more sensitive to how they are treated by nursing professionals and by the health team in general; therefore, unfavorable and/or unreceptive behaviors make them visit their children even less (8) .…”
Section: Discussionmentioning
confidence: 99%
“…To a mother, caring for an infant constitutes more than a simple performance of tasks. Rather, it involves recognising, accepting and bonding affectively with the child, activities that are a source of wellbeing for both [12]. One study [13] showed that the preparedness of mothers to care for their children after hospital discharge may reduce their anxiety and increase their self-confidence as primary caregivers, resulting in easier adjustment to the home environment.…”
Section: M6mentioning
confidence: 99%